Exploring gene editing using site-specific endonucleases as an approach to improve in vitro models of TNF Receptor-Associated Periodic Syndrome (TRAPS) - Alotiby, Amna (2017)
Tumour necrosis factor receptor-associated periodic syndrome is an autoinflammatory disorder caused by mutations in the tumour necrosis factor receptor-type 1 (TNFR1) gene, leading to misfolding of the TNFR1 protein and a resultant chronic inflammatory condition. This study aimed to explore the whether a more physiologically relevant model of TRAPS could be made by gene editing the cell’s endogenous TNFR1 genes. We utilized two site-specific nucleases, TALEN and CRISPR-Cas9 as gene editing tools. These nucleases are able to introduce double-strand DNA breakage at a pre-determined DNA sequence, resulting in gene modification, by two mechanisms: non-homologous end joining (NHEJ) or homology directed repair (HDR).